The Influence of Organizational Citizenship Behavior on Performance Through Job Satisfaction of Employees in The Production Section of PT. Suntory Garuda Beverage Sidoarjo - Fadillah, Moch Ivan; Nugrohoseno, Dwiarko (CV ODIS, 2024)
This research aims to test and analyze the influence of organizational citizenship behavior (OCB) on performance through job satisfaction of employees in the production department of PT. Suntory Garuda Beverage Sidoarjo. The research method used is a quantitative method, with a saturated sampling technique. The population is 189 production employees. The data analysis technique uses Partial Least Square (PLS). This research aims to determine the influence of Organizational Citizenship Behavior (OCB) on employee performance through job satisfaction at PT. Suntory Garuda Beverage Sidoarjo.